Construcción de un banco didáctico de torsión de ejes circulares y deflexión de vigas rectangulares hasta 1/2 in para cinco tipos de metales en la Facultad de Ingeniería Mecánica UAN. (2015)
The test beds for twist of circular axes and deflection of rectangular girders; will be implemented in the laboratories of the faculty of mechanical engineering at the Antonio Nariño university headquarters Neiva. The test bed will support in some areas of the Faculty of mechanical engineering, where through theoretical-practical classes students will experience failures of elements of machines such as: shafts and beams, and thus determine the type of material and the size recommended for power, torque, efforts and moments that will be subjected under loads at its points of support or resistance. The test bed consists of two systems in a compact and easy operation, where teachers and students, will be able to perform torsion circular shafts by means of verification of control instrument and a procedure where an actuator will exert force on the beam to bend the probe and check through 5 different types of materials (steel AISI1020 AISI 1040 (, Stainless 304, C14500 copper and aluminum 2014-O), the maximum resistance torque up to the fracture moment of the material.